Identifying the causal mechanisms of the quiet eye - Gonzalez, C. C.; Causer, J.; Miall, R. C.; Grey, M. J.; Humphreys, G.; Williams, A. M. (European Journal of Sport Science, 2016)
Scientists who have examined the gaze strategies employed by athletes have determined that longer quiet eye (QE) durations (QED) are characteristic of skilled compared to less-skilled performers. However, the cognitive mechanisms of the QE and, specifically, how the QED affects performance are not yet fully understood. We review research that has examined the functional mechanism underlying QE and discuss the neural networks that may be involved. We also highlight the limitations surrounding QE measurement and its definition and propose future research directions to address these shortcomings. Investigations into the behavioural and neural mechanisms of QE will aid the understanding of the perceptual and cognitive processes underlying expert performance and the factors that change as expertise develops.